A Parametric Study of LEM3D Based on Comparison with a Turbulent Lifted Hydrogen Jet Flame in a Vitiated Co-Flow. Issue 4 (2nd April 2020) - Grøvdal, Fredrik; Sannan, Sigurd; Chen, Jyh-Yuan; Løvås, Terese
ABSTRACT: A novel model, the hybrid RANS-LEM3D model, is applied to a lifted turbulent N2 diluted hydrogen jet flame in a vitiated co-flow of hot products from lean H2 /air combustion. In the present modeling approach, mean-flow information from RANS provides model input to LEM3D, which returns the scalar statistics needed for more accurate mixing and reaction calculations. The dependence of lift-off heights and flame structure on iteration schemes and model parameters are investigated in detail, along with other characteristics not available from RANS alone, such as the instantaneous and detailed species profiles and small-scale mixing. Two different iteration procedures, a breadth-first search (BFS) and a checkerboard algorithm, as well as parameters of the model framework are examined and tested for sensitivity toward the results. The impact of heat release and thermal expansion is demonstrated and evaluated in detail. It is shown for the current application that LEM3D provides additional details compared to the RANS simulation with a low computational cost in comparison with a conventional DNS simulation.